Structure development in confectionery products: importance of triacylglycerol composition - Santos, Jean Daniel dos (2018)
The objective of this thesis was to study the effect of the ratio symmetric/asymmetric TAG on the crystallization properties, storage stability and fat migration of fat blends. In order to do that, eight blends with varying ratios of symmetric/asymmetric TAG, but with an equal amount of saturated fatty acids (40%) were prepared. The preparation of the blends involved the mixing of different fractions of shea butter with high oleic sunflower oil. The ratio of symmetric/asymmetric TAG decreased from blend 1 to 8. These blends were crystallized at 15°C and 20°C and stored at various temperatures according to the experiment. The research was divided in four parts: part one focused on the determination of the composition of the starting materials and blends and their preparation, the investigation of the crystallization behaviour of the blends was done in part two while the storage stability was studied in part three, in part four the fat migration from hazelnut filling to tempered and untempered samples of the blends was studied. The starting materials and blends were characterized in terms of both fatty acid profile (through the use of GC) and TAG composition (through the use of HPLC). Based on the results of the starting materials the eight blends were prepared with different ratios of symmetric/asymmetric TAG. The crystallization behaviour was investigated using pNMR, DSC (both the isothermal and the stop and return method) and XRD. Regarding the DSC, results showed a two-step crystallization for all blends. The stop and return data gave an indication that polymorphic transitions occurred in most of the blends. This was confirmed by WAXD data that demonstrated a polymorphic transition from á to either â’ or â for almost all of the XRD experiments done. The storage stability of the blends was studied with hardness measurements and the analysis of the microstructure was done with polarized light microscopy. The hardness measurements showed that there was no direct pattern regarding the evolution of the hardness with time and/or ratio of symmetric/asymmetric TAG. It was observed that the two blends with the highest amount of SSO had the highest value of hardness directly after the crystallization at 15°C and the value drops substantially during storage whether it was stored at 18 or 23°C. The obtained values suggest that no post-hardening occurred. Through polarized light microscopy it was observed that blends 1, 2 and 3 formed big crystals imbedded in a matrix of small crystals, independently of the crystallization and storage temperature. Regarding to the other blends, they presented numerous crystals of very small size and very small gaps between them. In the study of the fat migration it could be observed that excluding blend 1, the effect of tempering on the prevention of the migration of the TAG seemed to be almost negligible. Between all of the blends, the tempered samples of blend 1 were the most effective in preventing the migration of TAG from the hazelnut filling to the stearic-based blend, while the untempered blend 1 was the less effective of them all.